FAKTOR FAKTOR YANG MEMPENGARUHI TINGKAT KEHAMILAN REMAJA USIA 15-19 DI KABUPATEN MANOKWARI SELATAN - Wambrauw, Yustina Lina Dina (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2016)
Based on SDKI West Papua Province (2012), 17 percent adolescents have become a mother, 13 percent adolencents have given birth and 4 percent in pregnancy for their first child. The step should be done is decribing about determination factors of early pregnancy of girl adolencents of papuan and non papuan adolescents. The research was conducting in South Manokwari Regency with primary and secondary data collection. Primary data is collected from quistionaire interview with women that have married in age 15 – 19 years old and secondary data collection is gained from research results and related institutions such as BKKBN and others. The results of the research are: a) the main factor of early pregnancy is uncontroled sexual intercourse and economic and social factor is low level of parents income; b) there is no different determination factors between papuan and non papuan in early pregnancy.